Testing the nonclinical Comprehensive In Vitro Proarrhythmia Assay (CiPA) paradigm with an established anti‐seizure medication: Levetiracetam case study - Annie Delaunois; François‐Xavier Mathy; Miranda Cornet; Vitalina Gryshkova; Chloé Korlowski; François Bonfitto; Juliane Koch; Anne‐Françoise Schlit; Simon Hebeisen; Elisa Passini; Blanca Rodriguez; Jean‐Pierre Valentin (Wiley, 2023)
Abstract Levetiracetam (LEV), a well‐established anti‐seizure medication (ASM), was launched before the original ICH S7B nonclinical guidance assessing QT prolongation potential and the introduction of the Comprehensive In Vitro Proarrhythmia Assay (CiPA) paradigm. No information was available on its effects on cardiac channels. The goal of this work was to "pressure test" the CiPA approach with LEV and check the concordance of nonclinical core and follow‐up S7B assays with clinical and post‐marketing data. The following experiments were conducted with LEV (0.25-7.5 mM): patch clamp assays on hERG (acute or trafficking effects), NaV1.5, CaV1.2, Kir2.1, KV7.1/mink, KV1.5, KV4.3, and HCN4; in silico electrophysiology modeling (Virtual Assay® software) in control, large‐variability, and high‐risk human ventricular cell populations; electrophysiology measurements in human induced pluripotent stem cell (hiPSC)‐derived cardiomyocytes and dog Purkinje fibers; ECG measurements in conscious telemetered dogs after single oral administration (150, 300, and 600 mg/kg). Except a slight inhibition (<10%) of hERG and KV7.1/mink at 7.5 mM, that is, 30‐fold the free therapeutic plasma concentration (FTPC) at 1500 mg, LEV did not affect any other cardiac channels or hERG trafficking. In both virtual and real human cardiomyocytes, and in dog Purkinje fibers, LEV induced no relevant changes in electrophysiological parameters or arrhythmia. No QTc prolongation was noted up to 2.7 mM unbound plasma levels in conscious dogs, corresponding to 10‐fold the FTPC. Nonclinical assessment integrating CiPA assays shows the absence of QT prolongation and proarrhythmic risk of LEV up to at least 10‐fold the FTPC and the good concordance with clinical and postmarketing data, although this does not exclude very rare occurrence of QT prolongation cases in patients with underlying risk factors.